Effects of cold SF6 plasma treatment on a-C:H, polypropylene and polystyrene - Amorim, Milena Kowalczuk Manosso [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Landers, Richard; Durrant, Steven F. [UNESP] (Elsevier, 2020)
The effects of cold SF6 plasma treatment on amorphous hydrogenated carbon (FA), polypropylene (PP) and polystyrene (PS) were investigated as functions of gas pressure and applied power. An anticipated increase in hydrophobicity was confirmed by the greater water contact angles, θ, observed after all the treatments. Under the best conditions θ was increased by 50.8°, 57.2° and 21°, respectively. A rise and fall in θ was observed as the pressure of SF6 was increased, this trend being most consistent for FA. Although the plasma treatments caused some changes in surface roughness, measured using profilometry, there were no clear correlations between this parameter and θ. As revealed by Energy Dispersive X-ray Spectroscopy (EDS) and X-ray Photoelectron Spectroscopy (XPS), the treated surfaces were fluorinated. As the degree of fluorination under optimal conditions was 2.2 at.%, 10.4 at.% and 36.3 at.% for the FA, PP and PS, respectively, this factor was not alone responsible for the observed increases in θ. Sulfur was attached to the surface of all the treated samples. The relative surface carbon content was reduced by the treatments. The main causes of the changes in θ upon treatment were the induced compositional and structural changes. Ageing for ten days caused a typical decrease in θ of ~10°, probably caused by rotation of hydrophobic surface groups into the surface.
Keywords: Ageing; Contact angle; Hydrophobicity; Polymers